A Mechanistic Systems Pharmacology Model for Prediction of LDL Cholesterol Lowering by PCSK9 Antagonism in Human Dyslipidemic Populations - K Gadkar; N Budha; A Baruch; J D Davis; P Fielder; S Ramanujan (Wiley, 2014)
PCSK9 is a promising target for the treatment of hyperlipidemia and cardiovascular disease. A Quantitative Systems Pharmacology model of the mechanisms of action of statin and anti‐PCSK9 therapies was developed to predict low density lipoprotein (LDL) changes in response to anti‐PCSK9 mAb for different treatment protocols and patient subpopulations. Mechanistic interactions and cross‐regulation of LDL, LDL receptor, and PCSK9 were modeled, and numerous virtual subjects were developed and validated against clinical data. Simulations predict a slightly greater maximum percent reduction in LDL cholesterol (LDLc) when anti‐PCSK9 is administered on statin background therapy compared to as a monotherapy. The difference results primarily from higher PCSK9 levels in patients on statin background. However, higher PCSK9 levels are also predicted to increase clearance of anti‐PCSK9, resulting in a faster rebound of LDLc. Simulations of subjects with impaired LDL receptor (LDLR) function predict compromised anti‐PCSK9 responses in patients such as homozygous familial hypercholesterolemics, whose functional LDLR is below 10% of normal. CPT Pharmacometrics Syst. Pharmacol. (2014) 3, e149; doi:10.1038/psp.2014.47; published online 26 November 2014